Is a contemporary theory of social entrepreneurship necessary for sustainable wealth creation? - Sarif, Suhaimi Mhd; Ismail, Yusof (2011)
The paper explores the need for a contemporary theory of social entrepreneurship for the contemporary knowledge/ innovation-based economy. Classical theories such as Cantillon's Theory of Entrepreneurship, Jean Baptise Say (1767-1832)'s theory of entrepreneurship, Frank Knight's Risk Bearing Theory of Entrepreneurship (1885-1972), Alfred Marshall’s Theory of Entrepreneurship (1980), Max Weber’s Sociological Theory in entrepreneurship (1864-1920) and Mark Casson's Economic Theory (1945) are based on the role economic agents to transform economic variables into economic products for the market. Proponents for contemporary social entrepreneurship argued that there is a need for the new theory given to the complexity and dynamism of today’s entrepreneurship. Thus, the study proposed research method and instrument to develop a contemporary theory for social entrepreneurship that is conclusive and generalisable. Prospective informants would be managers of technology parks, policy makers, government officers, and managers of technology-based firms. The expected results would develop a contemporary theory of social entrepreneurship.